Screening In Silico dan Penambatan Molekuler Senyawa Turunan 4-Hydroxytamoxifen (OHT) sebagai Kandidat Agen Anti Kanker Payudara terhadap Estrogen Receptor Alpha (ER-????) - Alfian Valentino Fernanda Putra Subhakti; Nindita Dwi Ambarwati; Nurul Qomaryah Kiswa; Dea Qoiril Ana; Nur Hanna Fahimah; Intan Asmi Saharani; Mutia Kafaa Ghania; Aleind Aloysius Gonzaga; Najma Tatsbita Satria; Putri Andini Sutejo; Imam Siswanto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Luminal breast cancer subtypes expressing Estrogen Receptor Alpha (ER-α) account for approximately 70% of breast cancer cases globally. Although hormonal therapy using the active ligand 4-hydroxytamoxifen (OHT) has been widely employed, its long-term efficacy is frequently hampered by drug resistance and adverse side effects. This study aims to design and evaluate, in silico, the potential of structurally modified OHT derivatives as more effective and selective ER-α inhibitor candidates. Ligand geometry optimization was performed using the semi-empirical PM6 method in Gaussian software. Molecular docking simulations were conducted using DOCK6 against the ER-α crystal structure (PDB ID: 3ERT), validated through a re-docking procedure of the reference ligand. Molecular interaction analysis was visualized in 2D/3D using BIOVIA Discovery Studio. Method validation showed high accuracy, with a Root Mean Square Deviation (RMSD) value of 1.032 Å (< 2.0 Å). Docking results revealed that the native ligand OHT-opt exhibited the best grid score (−59.47 kJ/mol), followed by pyrrolidine-OHT (−58.47 kJ/mol) and mono-fluoro-OHT (−56.11 kJ/mol). Interaction analysis showed that the mono-fluoro-OHT modification retains the essential hydrogen bond with the anchoring residue ARG101.A (2.716 Å) while forming a new hydrogen bond with GLU60 (2.668 Å) on helix 3 (H3). This new interaction may disrupt the receptor's allosteric conformation, potentially preventing transcriptional activation. This study concludes that structural modifications of OHT derivatives, particularly pyrrolidine-OHT and mono-fluoro-OHT, exhibit competitive binding affinities and hold strong potential to be developed as novel therapeutic agents for breast cancer, pending further validation through molecular dynamics simulations and in vitro experiments.